Turkish Rule In Northern India: During 13Th Century to 20Th Century: Exploring the Impact of Turkish Rule on Religious and Cultural History in Northern India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Two eras of Indian History, the 13thCentury and 20th Century marked a new beginning in the field ofHistoriography. The 13th Century is well known for the establishmentof the rule of early Turkish Sultans which ushered in an age in whichIndo-Persian historiography works of court chroniclers started a new phase inthe writing of Indian history. 20th century marked the dawn ofscientific historical writings which appeared in India and abroad by theefforts of British and Indian historian. During the 20th centurystudies on religious practices and traditions of the early Turkish rule havemade sufficient headway, in spite of the limited scope and availability ofcontemporary source materials. The study of medieval Islam as a religion with atotal impact on Hindustan was not wholly neglected by 20th centuryhistorians even when, as during the first forty years of this century,narrative political history dominated modern historiography on medieval India.An assessment of these writings initiated new insights and supplements theKnowledge already diffused through the writings of 20th centuryHistorian. A movement towards the study of the religious and cultural historyof the peoples of the sub-continent during the early Muslim period wasperceptible both in periodical literature appearing in English and alsooccasionally in monographs. Once again, it cannot be said that Britishhistorians have taken any prominent place in this shift of attention. Not muchwork had been done on the religious aspects of the early Turkish rule history.